Effects of active mobility act and parking places (amendment) bill on active mobility devices ridership - Lee, Andrew Khai Meng (2018)
Quick Response (QR) code geofencing has been proposed in Singapore to counteract indiscriminate parking of shared bicycles. The objective of this dual-student project was to study the effects of the Active Mobility Act and Parking Places (amendment) Bill on Active Mobility Devices (AMDs) ridership (discussed in this report), and indiscriminate parking (done by Mr Kang Kee Hong).